Comparative Study of Discovery Learning Models Based on Interpersonal Intelligence and Intrapersonal Intelligence on the Emotional Intelligence of Elementary School Students in Surabaya - Prastyo, Danang; Fanny, Arif Mahya; Susiloningsih, Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates the comparative effectiveness of Discovery Learning (DL) models based on interpersonal and intrapersonal intelligences in enhancing the emotional intelligence (EI) of elementary school students. Grounded in Gardner’s Multiple Intelligences theory and the constructivist paradigm, this research addresses the need for differentiated pedagogy that fosters both cognitive and affective development. A quantitative ex post facto design was employed involving 88 fourth-grade students from two public schools in Surabaya, Indonesia, who were categorized based on their dominant intelligence type. Emotional intelligence was assessed using a validated five-dimensional instrument comprising self-awareness, self-regulation, motivation, empathy, and social skills. The learning intervention consisted of eight sessions of Discovery Learning, with instructional activities tailored to each group’s intelligence orientation. Statistical analysis using an independent samples t-test revealed a significant difference in EI scores between the groups (p = 0.002), favoring students with interpersonal intelligence. These findings suggest that socially-oriented instructional models are particularly effective in promoting emotional competencies when aligned with students’ cognitive-emotional profiles. The study contributes to the discourse on adaptive learning design by demonstrating how intelligence-sensitive pedagogy can meaningfully enhance emotional intelligence in early educational settings.